1991
DOI: 10.1007/bf00177532
|View full text |Cite
|
Sign up to set email alerts
|

General protease and collagenase (IV) activity in C6 astrocytoma cells, C6 spheroids and implanted C6 spheroids

Abstract: Tumor growth is dependent on the ability of neoplastic cells to induce angiogenesis. Remodelling of blood vessels requires reconstruction of the collagen (type IV) and non-fibrous protein components of basement membrane. This study assessed the general protease and collagenase (IV) activities of C6 astrocytoma cells in monolayer and spheroid culture and C6 astrocytoma spheroids growing in vivo. Extracellular release of non-specific proteases and collagenase IV was maximal during early exponential cell growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Glioma cells have high levels of PAs [29,30] and also of metalloproteinases including type IV collagenase [18,31]. The invasive behavior of gliomas has been studied using various glioma invasion models [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma cells have high levels of PAs [29,30] and also of metalloproteinases including type IV collagenase [18,31]. The invasive behavior of gliomas has been studied using various glioma invasion models [12].…”
Section: Discussionmentioning
confidence: 99%
“…The potential biological significance of PAs in brain tumors has been suggested by others [14][15][16]. Furthermore, type IV collagenase and TIMP-2 are actively expressed in human gliomas [17,18]. In this study, we have asked whether the production of collagenases or PAs is closely correlated with the invasive activity of human glioma cells in culture.…”
Section: Introductionmentioning
confidence: 86%
“…Increased MMP levels and activity are commonly encountered in GBMs when these tumors are assessed using gel zymography or enzyme-linked immunosorbent type assays. 2,16,41,44,45,57,59 In previous immunohistochemical studies, however, conflicting results were reported in both the presence 45 and absence 41,46 of MMP-2 and MMP-9 in paraffin-embedded clinical specimens. In our study, wherein freshly prepared frozen sections were examined, we found a heterogeneous expression of both MMP-2 and MMP-9.…”
Section: Influence Of Mmps On Glioma Invasivenessmentioning
confidence: 96%
“…As a model of avascular growth saturation, the spheroid provides an interesting system for following the role of metabolic stress in inducing angiogenesis and measuring the impact of angiogenesis on tumour growth. The implanted spheroid model has been employed for following tumour angiogenesis in vivo (Farrell et al 1987;Coomber et al 1988;Vaithilingam et al 1991;Zwi et al 1994;Abramovitch et al 1995;Torres et al 1995) as well as antiangiogenic therapy . When implanted subcutaneously in nude mice, C6 glioma spheroids induce, within about 4 days, growth of vessels that approach the spheroid radially.…”
Section: Stress Induced Angiogenesis In Solid Tumours: the Multicellumentioning
confidence: 99%